P110 and P140 cytadherence-related proteins are negative effectors of terminal organelle duplication in Mycoplasma genitalium. - Oscar Q Pich; Raul Burgos; Enrique Querol; Jaume Piñol (PLoS ONE, 2009)
BACKGROUND:The terminal organelle is a complex structure involved in many aspects of the biology of mycoplasmas such as cell adherence, motility or cell division. Mycoplasma genitalium cells display a single terminal organelle and duplicate this structure prior to cytokinesis in a coordinated manner with the cell division process. Despite the significance of the terminal organelle in mycoplasma virulence, little is known about the mechanisms governing its duplication. METHODOLOGY/PRINCIPAL FINDINGS:In this study we describe the isolation of a mutant, named T192, with a transposon insertion close to the 3' end of the mg192 gene encoding for P110 adhesin. This mutant shows a truncated P110, low levels of P140 and P110 adhesins, a large number of non-motile cells and a high frequency of new terminal organelle formation. Further analyses revealed that the high rates of new terminal organelle formation in T192 cells are a direct consequence of the reduced levels of P110 and P140 rather than to the expression of a truncated P110. Consistently, the phenotype of the T192 mutant was successfully complemented by the reintroduction of the mg192 WT allele which restored the levels of P110 and P140 to those of the WT strain. Quantification of DAPI-stained DNA also showed that the increase in the number of terminal organelles in T192 cells is not accompanied by a higher DNA content, indicating that terminal organelle duplication does not trigger DNA replication in mycoplasmas. CONCLUSIONS/SIGNIFICANCE:Our results demonstrate the existence of a mechanism regulating terminal organelle duplication in M. genitalium and strongly suggest the implication of P110 and P140 adhesins in this mechanism.